Óleo de amêndoa de castanha de caju: obtenção, potenciais usos e desenvolvimento de produto - Oliveira, Gilleno Ferreira de (2022)
Cashew nut kernel oil (OACC) is a product with great potential for industrial use. It is obtained from broken kernels, using raw material of lower market value and presenting high nutritional appeal due to its lipid composition. However, to help make this product viable, it is important to define its quality characteristics and the sensory aspects of the product. Additionally, defining possibilities of uses in food formulations also becomes strategic, showing the versatility of the product and its potential for use by the market. Thus, the present work aimed to obtain cashew nut almond oil with high nutritional quality and evaluate the possibility of its use in the development of products with good sensory acceptance. For this, the oil obtained from cold mechanical extraction was characterized by analysis of acidity, peroxides, and analysis of smoke point, flash point, and oxidative stability through Rancimat. Sensory analyzes of the oil were also carried out, and an evaluation of market potential, using an electronic form of google forms. Subsequently, a Focus Group was carried out with 11 participants, where characteristics of the oil and possibilities of food applications were defined. Finally, the Focus Group selected a cashew nut and cocoa almond cream for formulation tests. After sensory analysis, the product was characterized through chemical, physical-chemical, and texture analysis. The results showed that the oil presented high quality since the Peroxide Index and Acidity Index were within the recommended by Brazilian legislation for cold pressed vegetable oils. In addition, the oil showed reasonable thermal stability, being able to be used even for the elaboration of products with the use of temperature. It presented a high sensorial acceptance and a possibility of very attractive market insertion from the results obtained in the market research. Concerning product development, it was possible to get a cream with sensory acceptance greater than 7 in all evaluated attributes, demonstrating the possibilities of using cashew nut almond oil as an ingredient in product development.